2020
DOI: 10.1039/d0ma00143k
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube enhanced dynamic polymeric materials through macromolecular engineering

Abstract: Dynamic covalent Diels-Alder chemistry was combined with multiwalled carbon nanotube (CNT) reinforcement to make strong, tough and conductive dynamic materials. Unlike other approaches to functionalizing CNTs, this approach uses Diels-Alder...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 34 publications
0
30
2
Order By: Relevance
“…Although equilibrium in this process favors formation of TM linkages (Figure 2), it is possible that one end of BMI cross-linker could undergo thiol-Michael addition with a thiol group on the polymer and the other end undergoes DA chemistry with MWCNT, ultimately resulting in effective reinforcement. 40 Unlike dual-dynamic materials, 7.5% crosslinked triply dynamic poly(EA 100 -UPyMA 2.5 -thiol 2.5 -FMA 2.5 ) showed that reinforcement can be achieved without necessarily losing extensibility (Figure 5d). Reinforced poly(EA 100 -UPyMA 2.5 -thiol 2.5 -FMA 2.5 ) had an average ε break of ∼2.20 mm/mm which is greater than all average ε break observed in Figure 5a−c (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although equilibrium in this process favors formation of TM linkages (Figure 2), it is possible that one end of BMI cross-linker could undergo thiol-Michael addition with a thiol group on the polymer and the other end undergoes DA chemistry with MWCNT, ultimately resulting in effective reinforcement. 40 Unlike dual-dynamic materials, 7.5% crosslinked triply dynamic poly(EA 100 -UPyMA 2.5 -thiol 2.5 -FMA 2.5 ) showed that reinforcement can be achieved without necessarily losing extensibility (Figure 5d). Reinforced poly(EA 100 -UPyMA 2.5 -thiol 2.5 -FMA 2.5 ) had an average ε break of ∼2.20 mm/mm which is greater than all average ε break observed in Figure 5a−c (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…54−56 Additionally, DA reaction facilitates effective reinforcement between functional furan side chains in this study and MWCNT by formation of DA adduct between MWCNT and polymer chains. 37,40 Integration of multiple types of dynamic bonds in polymer materials to synergistically harness their unique properties is rare and not well understood, especially the integration of more than two different orthogonal dynamic exchanges. 57 Hence, DPNs proposed in this study show distinctive dynamic properties that can be attributed to the unique contributions of each dynamic exchange employed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…aGlass transition temperature calculated in deflection point of DSC curve (2 nd heating). 40,41 bMelting temperature calculated as a minimum from DSC curve (1 st heating).cDecomposition temperature at 5% weight loss read from TGA curve.dDegradation temperature determined at a maximum of the DTG curve.ePercentage weight of residues after degradation.…”
Section: Resultsmentioning
confidence: 99%